Risky facilities: analysis of crime concentration in high-rise buildings - Benjamin Hutchins
This paper investigates the security of high rise high density accommodation at the Gold Coast – a premier Australian holiday destination. Surfers Paradise has one of the highest population densities in Australia at 3,279 persons per square kilometre and over 70 percent of the residential population live in buildings classed as high density within a mix of tourist apartments and units. The paper explores how the levels of place management and guardianship relate to the volume and mix of crimes occurring in high-rise apartment buildings. • Foreword: Current town planning and housing policies suggest that in the very near future, housing density in major Australian cities will be much higher than current levels. To date, little attention has been paid to how these policy shifts will impact levels of crime and fear of crime. The aim of this research is to contribute to the development of strategic policy for the secure management of high-density housing. By analysing actual rates and types of crime, guardianship levels, building management styles and perceptions of fear of crime, the research will reveal how planning policies and high-rise building management styles can coalesce to create safer vertical communities. The research focuses on high-rise apartments and touristic buildings on the Gold Coast (specifically Surfers Paradise) and identifies the disproportionate concentration of crimes among a handful of buildings. Results may help state and local governments in Australia to avoid repeating the housing policy mistakes experienced by other countries